The role of innate immunity in osteoarthritis: when our first line of defense goes on the offensive - Orlowsky, Eric W; Kraus, Virginia Byers (Journal of rheumatology, 2015)
Although osteoarthritis (OA) has existed since the dawn of humanity, its pathogenesis remains poorly understood. OA is no longer considered a "wear and tear" condition but rather one driven by proteases where chronic low-grade inflammation may play a role in perpetuating proteolytic activity. While multiple factors are likely active in this process, recent evidence has implicated the innate immune system, the older or more primitive part of the body's immune defense mechanisms. The roles of some of the components of the innate immune system have been tested in OA models in vivo including the roles of synovial macrophages and the complement system. This review is a selective overview of a large and evolving field. Insights into these mechanisms might inform our ability to identify patient subsets and give hope for the advent of novel OA therapies.